Storytelling Marketing and e-Wom: Effects On Purchase Decision Through Brand Image (HMNS Parfume Users) - Nashiroh, Abdillah Agustya Siwi; Sudarmiatin, Sudarmiatin; Hermawan, Agus (PT. EQUATOR SINAR AKADEMIA, 2025)
The purchase decision represents the point at which consumers finalize their choice of a product or service. People evaluate a number of criteria before making a decision, such as marketing campaigns, costs, product quality, brand perception, distribution strategies, and other aspects. Therefore, to improve purchasing decisions and build brand recognition, businesses need to plan their marketing efforts deliberately. For example, HMNS uses various marketing strategies, including storytelling marketing, to encourage consumer purchasing behavior. The reputation of the HMNS brand depends on maintaining product quality, such as the longevity of its fragrances. Adding these factors to the scope of research can provide a deeper understanding of how they influence consumer choices and brand perceptions. The study uses a quantitative technique in conjunction with a descriptive and explanatory methodology. Purposive sampling, a non- probability sampling approach, was used to choose the participants. 385 HMNS perfume users who follow the @HMNS Instagram account were included in the sample. SmartPLS 4.0 software was used to analyze the data using inferential analysis (also known as partial least squares, or PLS) and descriptive statistics. The findings show that: 1) Brand image is positively and considerably impacted by storytelling marketing; 2) e- WOM has a positive and large impact on brand image; 3) Purchase decisions are not much impacted by storytelling marketing; 4) Purchase decisions are positively and considerably influenced by e-WOM; 5) Purchase decisions are positively and significantly impacted by brand image; 6) Storytelling Marketing fully mediates the relationship between brand image and purchase decisions; 7) e-WOM somewhat mediates the influence of brand image on purchasing decisions. With research, we can explore more deeply that brand image can have a deeper influence on purchase decisions. Which can be proven by storytelling marketing, which cannot have a positive and insignificant influence on purchase decisions directly but with the existence of a brand image, this relationship becomes positive and significantly influence purchase decisions among HMNS parfume users.